A modified typology to classify secular NGOs and faith-based organisations in development contexts. Issue 2 (17th February 2020) - Frame, John
ABSTRACT: Within some contexts, distinguishing between faith-based organisations (FBOs) and secular NGOs may be challenging. While typologies for FBOs, and how they contrast to secular NGOs, exist in the literature, similarities and some shortcomings exist across them. This article introduces a modified typology that allows for a more nuanced understanding of secular organisations – namely those that accommodate religion in their programming. Significantly, the typology considers that "secular" is not always absent of religion. This analytical instrument is a contribution to future studies in development contexts where culturally valued religious elements may be integrated into secular organisations.